Entrepreneurial Innovation in Fashion: Case Studies on Business Models and Seed Capital Acquisition - Pandichelv, Umamaheswari (Journal of Global Economy, Business and Finance, 2026)
This paper argues that businesses in the fashion industry need to take note of the functioning of their business model in conjunction with the various sources of seed capital that exist in order to achieve growth. The first part highlights the need for investment opportunities and cash inflow in the fashion industry. It relies on statistical evidence about the fashion industry in the West and highlights why most firms are unable to achieve economies of scale. In the second part, the paper builds on that evidence and lays down various factors that make a business more investment-worthy: business model, management skill, credit restrictions, etc. The third part uses case studies to highlight the veracity of the analyses made hitherto. It also underscores the role of globalization and the transnational nature of capital. It concludes by noting how businesses need to focus on certain factors to make their business more appealing to various classes of investors and the importance of doing that in the contemporary world.